ERRORS IN INDONESIAN TO ENGLISH TRANSLATION TEXT MADE BY STUDENTS OF SMA NEGERI 13 PANGKEP - Amalya, Dwi Rizky; Syam, Ummi Khaerati; Anugrawati, Nunung; Sangkala, Ismail; Bte Abdul, Nurdevi (Fakultas Keguruan dan Ilmu Pendidikan, 2018)
The purpose of this research  to find out (1) The kinds of error in Indonesian to English translation text made by the students of SMA Negeri 13 Pangkep, and (2) The sources of error in Indonesian to English translation text made by students of SMA Negeri 13 Pangkep. This research is descriptive quantitative research. The subject of this research is the second year students of SMA Negeri 13 Pangkep. The second year students consists of five classes (105 students). The writer is taking 30 % as the sample, 30 students. The object of this research is errors in translating Indonesian to English text. The instrument of this research is a test (written text). The test is use to get data about the students’ error in Indonesian to English translation text. The result of this research, the writer found that the students make error in Indonesian to English translation text, the writer find out the kinds of error and the sources of error that made by students in translating a text Indonesian into English. The kinds of error are(1) Inversion of meaning students made about 65 error in text 1 and 68 error in text 2, (2) Omission of meaning made by students with 47 times occurrence and text 2 with 93 times occurrence, (3) Addition of meaning. The error made in text 1 with 78 times of occurrence and 62 error in text 2, (4) Deviation of meaning, students made error with 43 error in text 1 and 112 error in text 2. The sources of error made by students are (1) Morphological aspect, in translating a text students made errors. In text 1, students made error about 126 times of occurrence and 121 times of occurrence in text 2, (2)Lexical aspect, students made error with 424 error and then followed by text 2 with 350 error, and (3) Syntactic aspect, the error made by students about 425 error in text 1 and text 2 about 227 error. It can be concluded that second grade students who take Indonesian to English Translation at SMA Negeri 13 Pangkep is still making errors in translated a texts and dominant errors that students made is lexical aspect.